Students’ Perceptions of English as the Medium of Instruction in Indonesian Language for Foreign Speakers Classes - Rahmawati, Devi Suci; Savitri, Wiwiet Eva (Journal of English Language and Education, 2026)
English as the Medium of Instruction (EMI) has been widely implemented in higher education as part of internationalization efforts; however, its pedagogical role in BIPA (Bahasa Indonesia bagi Penutur Asing) classrooms remains underexplored. Most previous studies on BIPA primarily focus on instructional materials and linguistic achievement, leaving limited attention to how EMI functions in actual classroom practice and how learners perceive its use. This study investigates students’ perceptions of EMI in Level 1 BIPA listening and speaking classes at a university in Surabaya. Employing a qualitative case study design, data were collected through open-ended questionnaires and semi-structured interviews with 13 foreign students and were analyzed using thematic analysis. The findings indicate that students generally perceive EMI as helpful for improving comprehension, confidence, and classroom engagement, particularly at the beginner level, while still emphasizing the importance of Indonesian immersion for developing communicative competence. The study concludes that EMI can function effectively as instructional scaffolding to support beginner learners when applied strategically and progressively reduced as proficiency increases.